1979
DOI: 10.1002/food.19790230703
|View full text |Cite
|
Sign up to set email alerts
|

Flavour significant compounds in yeast autolysate Gistex X‐II powder. Part I. Acidic fraction

Abstract: Basic informations about the composition of yeast autolysate GistexLX-11-powder were obtained. The representative sample of volatile flavour-significant compounds was isolated. There were 29 substances identified in the acidic fraction of the isolate and the odour of this fraction was organoleptically evaluated. The organoleptic properties were mainly influenced by the presence of lower fatty acids and phenylacetic and 3-phenylpropionic acids. Two sulphur-containing heterocyclic acids, i. e. 2-thiophenecarboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The organic acids in YEs may be from yeast metabolism; on the other hand, they may be the oxidation products of the corresponding aldehydes for thermal oxidation during evaporation of YE manufacture. This is supported by the fact that Davídek et al identified a large number of acids in their aroma isolate of autolyzed yeast (AY) powder, and these probably derived from the corresponding aldehydes during the more rigorous thermal and oxidative drying AY to powder form.…”
Section: Resultsmentioning
confidence: 99%
“…The organic acids in YEs may be from yeast metabolism; on the other hand, they may be the oxidation products of the corresponding aldehydes for thermal oxidation during evaporation of YE manufacture. This is supported by the fact that Davídek et al identified a large number of acids in their aroma isolate of autolyzed yeast (AY) powder, and these probably derived from the corresponding aldehydes during the more rigorous thermal and oxidative drying AY to powder form.…”
Section: Resultsmentioning
confidence: 99%
“…This thiophene derivative is used as an intermediate in the synthesis of a thienylthiazolylthioaminoalcohol derivative, applied in the treatment of irregular impulse, heart sickness or hypertension [19], in the preparation of phosphorylamides derivatives, that possesses excellent antibacterial activity especially against Helicobacter pylori [20] and is applied in the synthesis of novel 3-substituted-2-oxindole derivatives that are analgesic, antiinflammatory and antiarthritic agents in the treatment of chronic inflammatory diseases [21]. Besides the therapeutic applications cited above, 2-thiophenecarboxylic acid and 5-methyl-2-thiophenecarboxylic acid were identified, for the first time, as volatile constituents of foodstuffs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the processing conditions, such as nature of the yeast and the presence of additional components, are likely to lead to flavour development, and the temperature of concentration or drying, could also have effects on the specific flavour profiles of yeast extract pastes. Munch and others studied several types of yeast extracts from different manufacturing sources and different aroma compounds were identified and characterised …”
Section: Introductionmentioning
confidence: 99%